LEADERSHIP IN CRISIS MANAGEMENT: BUILDING RESILIENT BUSINESS MODELS: Received: 13th September 2024 Revised: 12th October 2024, 28th November 2024, 12th December 20224 Accepted: 29th September 2024 - Baah, Richard Grover (PEOPLE: International Journal of Social Sciences, 2024)
This study explores the role of individual leadership in crisis management, focusing on how different leadership styles contribute to the development of resilient business models. Through cross-cultural and cross-sectoral case studies, the research identifies transformational, transactional, servant, and situational leadership styles as key factors in navigating crises. The findings suggest that transformational and servant leadership are particularly effective in fostering resilience, while transactional leadership, although useful in the short term, may require supplementation for long-term success. The study underscores the importance of cultural and sectoral contexts in shaping leadership practices and offers future directions for research in leadership development and crisis preparedness.